Kecukupan Modal, Pembiayaan Bermasalah, Bagi Hasil, Modal Intelektual dan Profitabilitas Bank Syariah di Indonesia - Kurnia, Kurnia; Inawati, Wahdan Arum; Husnaini, S. Ja’far (E-Jurnal Akuntansi; Vol 32 No 9 (2022), 2022)
This study examines the effect of capital adequacy ratios, non-performing financing, profit-sharing financing and intellectual capital on profitability. This study uses quantitative methods with a sample of ten Islamic Commercial Banks registered with the Financial Services Authority for the period 2014-2019. Based on research data, panel data regression analysis was used to determine the relationship between research variables. Processing data using Software Eviews. The study found that only non-performing financing variables had an effect on profitability. Researchers provide recommendations to Islamic banks to be able to rearrange their capital in order to reduce the risk of non-performing financing. Keywords: Capital Adequacy Ratio (CAR), Intellectual Capital, Non-Performing Financing (NPF), Profitability and Profit Share Financing.